Nano-curcumin Effects on Ischemic Stroke clinical outcomes and Interleukin-6 Levels: Pilot Randomized Clinical Trial - Zeinab Ehtiatkar; Alia Saberi; Samaneh Ghorbani Shirkouhi; Mozaffar Hosseininezhad; Shahrokh Yousefzadeh-Chabok; Yaser Moadabi; Ashkan Karimi; Haniyeh Shadrou Gharani; Sasan Andalib (Caspian Journal of Neurological Sciences)
Background: Accumulation of inflammatory factors in the stroke area results in brain tissue damage and a patient’s disability. It has been demonstrated that curcumin has neuroprotective effects. Objectives: This study aims to evaluate the effects of nano-curcumin, a more stable and soluble form than the common curcumin, on the National Institutes of Health Stroke scale (NIHSS) and modified Rankin scale (mRS) scores and interleukin-6 (IL-6) serum levels in ischemic stroke patients. Materials & Methods: Forty ischemic stroke patients were randomly divided into two groups of nano-curcumin and control, with 20 patients in each group. The curcumin group received nano-curcumin with a dose of 80 mg/d for one month, and the control group received placebo. Neurological disabilities were assessed by NIHSS and mRS over three time points. IL-6 serum levels were evaluated over two time points. Infarct area volume was evaluated in two time points. Results: NIHSS and mRS scores were significantly lower in the curcumin group than in the control group (P=0.038 and P<0.001, respectively). Serum levels of IL-6 were significantly lower in the curcumin group than in the controls (P<0.001). The cerebral infarct volume did not change significantly one week after the treatment with curcumin. Conclusion: Nano-curcumin improves the stroke clinical symptoms in ischemic stroke patients, as indicated by the reduction of NIHSS and mRS, in addition to a decrease in serum levels of IL-6.